THE ROLE OF VILLAGES IN CORRUPTION PREVENTION BUDGET FOR COVID-19 HANDLING AND PREVENTION FUNDS IN NORTH SUMATERA - Sitorus, Nanang Tomi; Zulyadi, Rizkan (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
Prevention and handling of Covid-19 in North Sumatra requires a very large budget. The funds intended for the public need to be supervised in the distribution of assistance so that corruption does not occur. The form of punishment imposed on perpetrators of criminal acts of corruption during this pandemic is the death penalty in accordance with the applicable laws and regulations. The purpose of this research was carried out because the budget allocated for handling Covid-19 by the government was very large, so it is necessary to have a monitoring system by all parties so that there is no criminal act of corruption. The type of research used is normative juridical research and the nature of the research used is descriptive analytical. Based on the results of the research, the budget transparency of funds for people affected by the Covid-19 pandemic has been carried out with the right target and transparency for the people affected by Covid-19. Law enforcement efforts to supervise and handle the Covid-19 fund budget involve law enforcement officials, village officials and all elements of society so that there is no unrest between one community and another.